Recurrent Severe Hypoglycemia in a 43 Year Old Extreme Obese Woman with Insulinoma: A Case Report - Zaki Mita Kusumaadhi; Farah Hendara Ningrum; Bambang Satoto; Titik Yuliastuti; Y. F. Rahmat Sugianto; Etisa Adi Murbawani; Didik Indiarso; Erik Prabowo; Tania Tedjo Minuljo; Yohana Prima Ceria Anindita; K. Heri Nugroho HS; Meira Dewi Kusuma Astuti (PP PERKENI, 2025)
Insulinomas are very rare neuroendocrine tumors (4 cases per million individuals per year) leading to insulin hypersecretion and occurring more often in women at any age. A 43 year old extreme obese woman was referred to Dr Kariadi General Hospital with complaints history of repeated unconsciousness due to recurrent episodes of symptomatic severe hypoglycaemia (previously been hospitalized several times in regional hospitals in last six years). Physical examination: Body Mass Index Class II obesity (Asia-Pacific). Laboratory: recurrent hypoglycaemia (random blood glucose range 30-50 mg/dL), Fasting Blood Glucose 105 mg/dL (n: 80-109), 2 hours Postprandial Blood Glucose 44 mg/dL (n: 80- 140), C-peptide levels (taken during hypoglycaemia) 13.59 ng/ml (n:1.1-4.4). Abdominal Ultrasonography : grade 2 fatty liver, Fibroscan: no fibrosis or steatosis, Plain Head MSCT: no visible abnormalities, contrast abdominal magnetic resonance imaging: solid lesion in the body of pancreas (AP 1.2 x LL 1.2 x CC 1.3 cm) tends to be a picture of insulinoma. Patient underwent distal pancreatectomy with immunohistochemical results of an insulinoma. Post surgery the patient never had hypoglycaemia. We described a 43 year old extreme obese woman with recurrent episodes of symptomatic severe hypoglycaemia. Laboratory (low random blood glucose, high C-peptide) and imaging examinations (solid lesion in the body of the pancreas on Contrast Abdominal MRI) support the diagnosis of insulinoma. Surgery is the treatment of choice for insulinomas. Patients with recurrent severe hypoglycemia, increase in C-peptide levels and solid lesion in pancreas are clinical manifestations of Insulinoma.